Zoophytophagous predator‐induced defences restrict accumulation of the tomato spotted wilt virus. Issue 2 (14th August 2019) - Bouagga, Sarra; Urbaneja, Alberto; Depalo, Laura; Rubio, Luís; Pérez‐Hedo, Meritxell
Abstract: BACKGROUND: The use of zoophytophagous predators in protected crops has been widely adopted to manage pests in southern Europe. We hypothesized that plant defence responses would be induced by zoophytophagous predators and this induction could affect plant virus occurrence; the phytophagy of these predators induces plant defences similarly to that of viral infection. Therefore, we evaluated whether or not mirid predator‐activated plant defences limited the accumulation of Tomato Spotted Wilt Virus (TSWV) in mechanically infected sweet pepper. RESULTS: Our results revealed TSWV accumulation in mirid‐punctured plants to be significantly lower than in intact plants. This is most likely associated with the upregulation of the jasmonate acid pathway triggered by mirid phytophagy. CONCLUSION: Activation of induced defences by mirid predators has been demonstrated for the first time to limit the accumulation of TSWV in sweet pepper. This novel approach can offer new control strategies for the management of plant diseases. © 2019 Society of Chemical Industry Abstract : TSWV accumulation in mirid‐punctured plants is significantly lower when compared to intact plants. This is probably associated with the upregulation of the jasmonate acid pathway triggered by mirid phytophagy.